(untitled) (Panacea Journal of Medical Sciences, 2024)
Background: Thrombocytopenia is the condition in which the platelets counts are less than few lakhs and cause the symptoms of the bleeding. The drugs which are used as therapeutic for the management of the diseases, due to adverse effects causes thrombocytopenia. The present study aims to find the prevalence of the drug induced thrombocytopenia in various cities in India Materialsa nd Methods : A cross sectional survey study design used to identify the prevalence rate of the drug induced thrombocytopenia in Lakhimpur 1050 samples, Panipat 1465 samples, Sonipat 815 samples, Gohana 845 samples, Delhi 1265 cities in India a total 5440 samples from 5 cities in north India were selected from different diagnostic centers. Results: The present study found that in Lakhimpur total 1050 samples were collected of them 39 samples, in Panipat total 1465 samples were collected 66 samples, in Sonipat total 815 samples were collected of them 63 samples, in Gohana total 845 samples were collected of them 40 samples and in Delhi total 1265 samples were collected of them 53 samples were drug induced thrombocytopenia respectively. The overall prevalence of drug induced thrombocytopenia is 4.7%. Conclusion: Drug induced thrombocytopenia is result of the adverse effect of various group of drugs used as therapeutic management and the prevalence of the drug induced thrombocytopenia is essential to manage and prevent the complication. The present study identified the prevalence of drug induced thrombocytopenia in selected North India.